Retail analytics : the secret weapon - Cox, Emmett, 1957- (Hoboken, N.J. : Wiley, 2012)
'Retailers have collected a huge amount of data but they do not know what to do with it. This book is designed not only to provide a broad understanding of retail but show how to use the data that these companies have. Each chapter covers a different focus of the retail environment from retail basics and organization structures to common retail database designs. Numerous cases studies and examples are given throughout. In addition, within each chapter the importance of analytics and data is examined'--
Includes index.
Keywords: Retail trade; Retail trade -- Statistics; Retail trade -- Case studies; BUSINESS & ECONOMICS / Industries / Retailing